If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11w + 6 = -38 Reorder the terms: 6 + -11w = -38 Solving 6 + -11w = -38 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -11w = -38 + -6 Combine like terms: 6 + -6 = 0 0 + -11w = -38 + -6 -11w = -38 + -6 Combine like terms: -38 + -6 = -44 -11w = -44 Divide each side by '-11'. w = 4 Simplifying w = 4
| .24.14= | | 10=-2p-2+3p | | -4=-4p-11+5p | | M/-16=-9 | | y-9=15(x-5) | | 13=3p-15-2p | | x^2+24x-23=0 | | 8x^2-28x+98=0 | | 8x^2-28+98=0 | | 38x-14=20 | | 2(x-2)=-3x+21 | | 2+3.8= | | 3(2a-4)= | | 2(x-2)=-3+21 | | 3a+50=140 | | -9-6=8+x | | (y^2-7)(5y^2-5y+6)= | | 2+38= | | -13=7p-12-6p | | 36r^9-9r^6+54r^3= | | 7(3x-4)=17x | | x+6/5+x-1/4=2 | | 11=8p-14-7p | | n^2=4n+5 | | 1/2y-1/3x-1=0 | | -3=3p+11-2p | | 6=-6p-10+7p | | a+3ab-4ab= | | 3x-5+9x=-15 | | 8x^3-49x^2+6x=0 | | -8+10=9x+17 | | 1+a+x^2=p |